Towards Immunotherapy-Induced Normalization of the Tumor Microenvironment - Melo, Vinicio; Bremer, Edwin; Martin, John D. (Frontiers in Cell and Developmental Biology, 2022)
Immunotherapies modulate the function of immune cells to eradicate cancer cells through various mechanisms. These therapies are successful across a spectrum of cancers, but they are curative only in a subset of patients. Indeed, a major obstacle to the success of immunotherapies is the immunosuppressive nature of the tumor microenvironment (TME), comprising the stromal component and immune infiltrate of tumors. Importantly, the TME in most solid cancers is characterized by sparsely perfused blood vessels resulting from so-called pathological angiogenesis. In brief, dysregulated development of new vessels results in leaky tumor blood vessels that inefficiently deliver oxygen and other nutrients. Moreover, the occurrence of dysregulated fibrosis around the lesion, known as pathological desmoplasia, further compresses tumor blood vessels and impairs blood flow. TME normalization is a clinically tested treatment strategy to reverse these tumor blood vessel abnormalities resulting in stimulated antitumor immunity and enhanced immunotherapy efficacy. TME normalization includes vascular normalization to reduce vessel leakiness and reprogramming of cancer-associated fibroblast to decompress vessels. How immunotherapies themselves normalize the TME is poorly understood. In this review, we summarize current concepts and progress in TME normalization. Then, we review observations of immunotherapy-induced TME normalization and discuss the considerations for combining vascular normalizing and immunotherapies. If researchers could more completely normalize the TME, immunotherapies could be more effective in more patients.